(untitled) - Munford, Paul (Indianapolis, IN, 2016)
Mastering Autodesk Inventor 2016 and Autodesk Inventor LT 2016 is a complete real-world reference and tutorial for those learning this mechanical design software. With straightforward explanations and practical tutorials, this guide brings you up to speed with Inventor in the context of real-world workflows and environments
Keywords: Autodesk Inventor (nguồn điện),Mô hình kỹ thuật,Kỹ thuật đồ họa,Autodesk Inventor (Electronic resource),Engineering models,Engineering graphics; Xử lý dữ liệu,Data processing